CAN FEMINISM BE CONSIDERED A MAINSTREAM THEORY OF INTERNATIONAL RELATIONS? - Mita Yesyca (Kajian Asia Pasifik, 2017)
The growth of Feminism which has given rise to a new study in the International Relations (IR) field is worth to follow. Not only since it is able to contribute to the academic discipline of IR in theoretically challenging the traditional approach to understand the world politics, but also since it is able to contribute practically because of its nature as a socio-political movement. Nevertheless, in the IR itself there is always a question concerning the possibility of Feminism to be considered a mainstream theory. This article tries to discuss the theoretical contribution of, as well as some issues followed, the development of Feminism in the study of international relations all this time. It finally argues that Feminism can be considered a mainstream theory of international relations so long as there are conversations between traditional theories of international relations and feminists theories of international relations. Keywords: Feminism, International Relations, mainstream theory Abstrak Perkembangan Feminisme yang telah melahirkan suatu kajian baru dalam ilmu Hubungan Internasional (HI) layak untuk disimak. Tak hanya karena ia mampu menyumbang secara teoritis kepada disipilin ilmu HI dalam menantang pendekatan tradisional untuk memahami politik dunia, tetapi juga karena ia mampu menyumbang secara praktis mengingat bahwa sejatinya ia merupakan sebuah gerakan sosial-politis. Meski demikian, dalam HI sendiri selalu ada pertanyaan mengenai peluang Feminisme untuk diterima sebagai sebuah teori yang lazim. Tulisan ini mencoba mendiskusikan sumbangan teoritis dari, sekaligus perdebatan-perdebatan yang mengikuti, perkembangan Feminisme dalam kajian hubungan internasional selama ini. Argumen yang dibangun pada akhirnya ialah bahwa Feminisme dapat dianggap sebagai sebuah teori tentang hubungan internasional yang lazim sepanjang terdapat percakapan antara teori tentang hubungan internasional tradisional dan teori feminis tentang hubungan internasional. Kata kunci: Feminisme, Hubungan Internasional, teori mainstream